Implementation Analysis of the Marketing Mix Strategy for the Begos Restaurant, Makassar City - Gumelar, A.; Ridwan, M.; Hastang, H.; Bahtiar, B.; Windiana, W. (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2025)
This study aims to analyze the implementation of the 7P marketing mix strategy (Product, Price, Place, Promotion, People, Process, Physical Evidence) at Bebek Goyang Sulawesi Restaurant in Makassar City. A descriptive research method with a qualitative approach was employed, where data were collected through interviews and questionnaires administered to management and consumers. The findings reveal that most marketing mix elements have been effectively implemented, particularly regarding product quality, strategic location, and digital media promotions. However, some areas require improvement, such as the pricing strategy, which is perceived as less competitive, and the cleanliness of physical facilities. From the consumers' perspective, the